2022
DOI: 10.1038/s41467-022-33605-1
|View full text |Cite
|
Sign up to set email alerts
|

Scleral PERK and ATF6 as targets of myopic axial elongation of mouse eyes

Abstract: Axial length is the primary determinant of eye size, and it is elongated in myopia. However, the underlying mechanism of the onset and progression of axial elongation remain unclear. Here, we show that endoplasmic reticulum (ER) stress in sclera is an essential regulator of axial elongation in myopia development through activation of both PERK and ATF6 axis followed by scleral collagen remodeling. Mice with lens-induced myopia (LIM) showed ER stress in sclera. Pharmacological interventions for ER stress could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…The most common animal models of myopia are form-deprivation myopia (FDM) and lens-induced myopia (LIM) [ 2 4 ]. Recently, our team found that mice with LIM showed endoplasmic reticulum (ER) stress in the sclera, which is similar to the results of other researchers using the FDM model [ 5 , 6 ]. Furthermore, we previously showed that scleral ER stress causes myopia [ 5 , 6 ].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The most common animal models of myopia are form-deprivation myopia (FDM) and lens-induced myopia (LIM) [ 2 4 ]. Recently, our team found that mice with LIM showed endoplasmic reticulum (ER) stress in the sclera, which is similar to the results of other researchers using the FDM model [ 5 , 6 ]. Furthermore, we previously showed that scleral ER stress causes myopia [ 5 , 6 ].…”
Section: Introductionsupporting
confidence: 86%
“…Recently, our team found that mice with LIM showed endoplasmic reticulum (ER) stress in the sclera, which is similar to the results of other researchers using the FDM model [ 5 , 6 ]. Furthermore, we previously showed that scleral ER stress causes myopia [ 5 , 6 ]. This clearly indicates a correlation between myopia and ER stress.…”
Section: Introductionsupporting
confidence: 86%
“…Recent studies have indicated that hypoxia might be one of the key mechanisms inducing abnormal ECM remodeling in the regulation of scleral ECM during myopia (Wu et al 2018 ). Additionally, our previous findings demonstrated that endoplasmic reticulum stress in the sclera might play a significant role in the expression of ECM proteins (Ikeda et al 2022 ). However, due to the intricate composition of the ECM, elucidating the role of specific ECM genes in the myopia process is challenging, and further exploration of the associated mechanisms is warranted.…”
Section: Discussionmentioning
confidence: 97%
“…SaCas9 or guide RNA (Supplementary Table T2 ) against THBS1 expression cassettes were constructed and packaged into AAV-DJ vectors (titer > 1.0E + 13 GC/ml) by Vector Builder as described in previous reports (Ikeda et al 2022 ; Zhao et al 2018 ). The mice were randomly assigned to three groups: a sham-operation group (anaesthetized and had a ‘dry’ needle inserted with no injection), a group injected with scramble guide RNA, and a group injected with gThbs1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation